The finding of bryozoans from the lower Pliocence of Crete (Maronia - Sitia). Systematics - Paleoecology - ΜΑΡΚΟΠΟΥΛΟΥ- ΔΙΑΚΑΝΤΩΝΗ, Α.; ΜΙΡΚΟΥ, Ρ. Μ.; ΠΑΠΑΔΑΚΗ, Μ. (Bulletin of the Geological Society of Greece, 2018)
A rich fauna of Bryozoa from the Lower Pliocene of the Maronia district (location of Hagios loannis) had been studied. 47 species have been indentified belonging to the Cyclostomata (16) and Cheilostomata (31). This study allows to precise - based on the Foraminifers - the distribution of Bryozoans in this area of the South- East Mediterranean. Based on the zoarial forms, the bathymetry, the temperature and the bottoms, where some species live yet now, we attempt to give a reconstruction of the paleoenvironments. The Lower Pliocene age is based on the stratigraphie distribution of the following Foraminifers: Amphistegina lessonii, Bolivina antiqua, μBulimina cf. minima, Cibicides refiilgens, Globigerinoides extremus, Globigerinoides nepenthes, Globigerinella pseudobesa, Globulina fissicosta, Heterolepa dertonensis, Neogloboquatrina ci.acostaensis, Rectuvigerina siphogenerinoides, Sphaeroidinellopsis seminulina.